Antibiotic Use Pattern of Surgical Site Infection Prophylaxis in Surgical Wards of a Teaching Hospital in Shiraz, Iran - Laleh Mahmoudi; Azadeh Mahdavinia; Shokoufe Khajooi; Asal Zargari- Samadnejad; Iman Karimzadeh (Shiraz University of Medical Sciences, 2023)
Despite the need to use prophylactic antimicrobials to prevent infection at the surgical site, in many cases the use of prophylactic antibiotics is inappropriate. The aim of this study was to determine the pattern use of surgical site infection antibiotics prophylaxis based on standard guidelines in a teaching hospital in Shiraz. In this observational study, information of 338 patients from May to October 2020 received prophylactic antibiotics before surgery at Shahid Faghihi Hospital affiliated to Shiraz University of Medical Sciences was reviewed. Type of antibiotics, combination of antibiotics, dose and duration of treatment for each patient were defined based on both the American Society of Health-System Pharmacists (ASHP) and the National Ministry of Health and Medical Education of Iran guidelines for antimicrobial prophylaxis in surgery. Of the total 338 patients included in this study, only 27.5% received antibiotic prophylaxis according to standard guidelines. The most commonly used antibiotic class for surgical site infection prophylaxis was the first generation cephalosporins. The highest rate of antibiotic prophylaxis appropriateness was identified in the urology ward (11.53%). Few cases of antibiotic prophylaxis have shown complete compliance with the standard guidelines in this preliminary report.